From Gaia to selfish genes : selected writings in the life sciences - Barlow, Connie C. (Cambridge, Mass. : MIT Press, 1991)
Anthology of excerpts from the writings of leading scientists on the ideas driving contemporary biological research.
Includes bibliographical references (p. [249]-256) and index.
Adult.
Adult
Keywords: Biology -- Philosophy; Biology -- Research; Biology -- Philosophy; Biology -- Research